Effects of the incident angle of branch pipe on the thermal mixing of impinging jets in T-junctions. (April 2022) - Nan, Zezhao; Gu, Mingzhou; Li, Yaru; Zhang, Keyuan; Wang, Naihua
Highlights: Impinging jet in 90° and 45° T-junctions are studied by experiment and simulation. Mixing and temperature fluctuation characteristics are presented. Two temperature fluctuation mechanisms are proposed. Dominant frequencies and frequency ranges of high fluctuation energy are shown. Abstract: Visualization experiments and Large Eddy Simulations (LES) of mixing in T-junctions were carried out and analysed in terms of mixing and temperature fluctuations characteristics. T-junctions with 90° and 45° incident angles of branch pipe were applied in experiments. The near-wall temperature was measured using novel thermocouples, and the experimental data has validated the numerical simulations. From the perspective of mixing quality, the mixing in the 90° T-junction shows a better uniformity. Moreover, the LES results indicate that the temperature fluctuations are dominated by the large-scale vortices in the main pipe. The incident angle has an effect on the behaviours of windward shear layer vortices, but it hardly affects the quasi Karman vortex series. The first dominant frequencies determined by windward shear layer vortices are 9.5–10.5 Hz and 20–23 Hz in 90° and 45° T-junctions, respectively. The quasi Karman vortex series determine the second dominant frequency, which is the same in these two T-junctions. Two main near-wall areas where the temperature fluctuate most severely were identified. One is the upper near-wall area, and the other is at the spanwise side. Temperature fluctuations of 45° T-junction contain lower energy in the two areas.